Effect of polyethylene terephthalate tongue scraper in removing tongue coating (Research, Society and Development, 2024)
The objective of this research was to compare a tongue scraper obtained from polyethylene terephthalate (PET) bottles with a commercial model (COM). A parallel, controlled and randomized design was used. Of the 61 volunteers from the Department of Dentistry at the Federal University of Sergipe, 30 met the inclusion and exclusion criteria for random distribution into 2 groups: PET (n=15) and COM (n=15). At the initial appointment, the Winkel Tongue Coating Index (ISL-W) was measured before (T0) and immediately after (T1) removal of the tongue coating carried out by the professional, who provided instructions for home use of the scraper twice a day. After 14 days, ISL-W was measured at T0 and T1, with the participant removing the coating. Of the 30, 1 in the COM group did not return for a 14-day appointment. Data obtained at T0 and T1 were subjected to the paired Student's t-test (α=0.05). The differences between T0 and T1 were transformed into percentage values and analyzed with the unpaired Student's t- test (α=0.05). T0 data from the initial appointment and after 14 days were subjected to the paired Student's t-test (α=0.05). The results indicated that the 2 scrapers significantly reduced ISL-W (P